Global soil organic and inorganic carbon vulnerability in response to irrigation - Qi Tang; Yanqing Xu; Li Hua; Yiyun Chen (Communications Earth & Environment)
Abstract Irrigation exerts a strong influence on carbon dynamics in agroecosystems. However, global patterns of soil organic carbon (SOC) and soil inorganic carbon (SIC) responses to irrigation remain insufficiently characterized. Here, we synthesized 223,593 observations to derive 2217 representative soil profile measurements and estimated the differential effects of irrigation on SOC and SIC. Our results show that soil carbon responses to irrigation vary with soil depth and are related to the amount of irrigation water applied. Specifically, SOC and SIC of cropland increased by 127% and 57.09%, respectively, under 200–300 mm irrigation compared to the reference study sites. In global upscaling experiments, we mapped the vulnerability distribution of SOC and SIC losses in irrigated cropland by applying a meta-forest model. We found that 54.58% of stable cropland areas were projected to experience SOC losses, and 60.22% were projected to experience SIC losses, under long-term continuous irrigation, with SIC at greater global risk. These findings highlight the need for strategic consideration of carbon sequestration potential in irrigation management to support climate adaptation efforts.